Islamic Republic of Pakistan : Leveling the Playing Field - World Bank (World Bank, Washington, DC, 2020)
This Systematic Country Diagnostic (SCD)—the first to be conducted in Pakistan—is aimed at informing Pakistan’s ongoing structural reform process and providing an analytical base for the World Bank Group’s (WBG) engagement moving forward. It presents a timely and evidence-based assessment of the constraints that the country needs to address, and the opportunities that it can embrace, to sustainably accelerate progress toward the goals of ending extreme poverty and promoting shared prosperity. The SCD, while focusing on developments in the past two decades, builds on the extensive analytical work conducted under the “Pakistan@100 – Shaping the Future” study and reflects inputs from the WBG’s previous and ongoing stakeholder consultations. This SCD was completed before the COVID-19 pandemic struck, and the analysis presented in the report primarily uses data released up until end-February 2020.